CGIAR Driving Food Systems Transformation: A Look at the Alliance of Champions for Food Systems Transformation (ACF) and the Technical Cooperation Collaborative (TCC) - CGIAR Climate Change Impact Platform (CGIAR Climate Change Impact Platform, 2024)
The 2023 COP28 conference marked a pivotal moment in the global conversation on food systems. The event underscored the critical role of food systems in addressing climate change, biodiversity loss, and food security. CGIAR is actively involved in various initiatives that emerged from COP28 to drive positive change in this area - including the Alliance of Champions for Food Systems Transformation (ACF) and the Technical Cooperation Collaborative (TCC).